New Careers in Nursing (NCIN) Alumni Survey, 2013 - Millett, Catherine ([Verlag nicht ermittelbar], 2016)
This survey was conducted as part of an evaluation of New Careers in Nursing (NCIN), a national scholarship program of the Robert Wood Johnson Foundation for nursing students from underrepresented groups in nursing or from disadvantaged backgrounds. It was founded in 2008 to help alleviate the nursing shortage, increase the diversity of nursing professionals, expand capacity in baccalaureate and graduate nursing programs, and enhance the pipeline of potential nurse faculty. The survey explored NCIN alumni employment in nursing, career aspirations and advanced education after they graduated from their nursing degree program. Additionally, respondents were asked to rate various aspects of their nursing degree program. Other topics covered by the survey include leadership and mentoring experiences, the reputation of NCIN among employers, student loans and alumni demographics.